Insulin‐like growth factor 1 sustained‐release collagen on urethral catheter prevents stricture after urethral injury in a rabbit model. (25th February 2019) - Shinchi, Masayuki; Kushibiki, Toshihiro; Mayumi, Yoshine; Ito, Keiichi; Asano, Tomohiko; Ishihara, Miya; Horiguchi, Akio
Abstract : Objectives: To evaluate the preventive effect of an insulin‐like growth factor 1 sustained‐release collagen urethral catheter on urethral stricture after urethral injury in a rabbit model. Methods: We made urethral catheters coated either with insulin‐like growth factor 1 impregnated collagen or with only collagen, and we divided 19 male Japanese white rabbits into three groups according to the kind of catheter inserted immediately after the rabbit's urethra was injured by electrocoagulation. Group 1 ( n  = 7) had a catheter coated with insulin‐like growth factor 1 impregnated collagen inserted; group 2 ( n  = 7) had a catheter coated with only collagen inserted; and group 3 ( n  = 5) had an uncoated catheter inserted. A total of 14 days later, the injured urethras were evaluated by urethrography and urethroscopy, and were also histologically examined. Results: Urethrography showed that the ratio of the urethral lumen diameter in injured urethra to that in normal urethra was the largest in group 1 ( P  < 0.0001). In addition, five of the seven rabbits in group 1 (71.4%) had a urethral lumen large enough for passage of a urethroscope, a fraction larger than the corresponding fractions in groups 2 (57.1%) and 3 (20%). On histological analysis, the injured area not covered with regenerated urethral epithelium tended to be smaller in group 1 than the other two groups, but the mean difference was not significant ( P  = 0.19). Conclusions: An insulin‐like growth factor 1 sustained‐release collagen urethral catheter significantly improves wound healing and prevents urethral stricture after urethral injury.